Succinate accumulation contributes to oxidative stress and iron accumulation in pentylenetetrazol-induced epileptogenesis and kainic acid-induced seizure. (October 2021) - Zhang, Yurong; Cui, Yaru; Cheng, Yao; Zhu, Wei; Zhang, Mengdi; Li, Shucui; Liu, Wenbo; Xin, Wenyu; Huang, Wei; Sun, Hongliu
Abstract: This study explored the role of succinate accumulation in the oxidative stress and iron accumulation in both pentylenetetrazol (PTZ)-induced epileptogenesis and kainic acid (KA)-induced status epilepticus (SE). The levels of succinate, oxidative stress, iron content, iron-related protein expression, and the severity of neuronal injury and seizures were measured in both models. We found that increased concentrations of succinate were associated with increased levels of oxidative stress, iron content, iron regulator protein, and iron importer divalent metal transporter 1, as well as decreased levels of iron exporter ferropotin 1. Aggravated neuronal injury was observed in the hippocampi and cortices of both models. The cell-permeable molecule dimethyl malonate (DM), a competitive inhibitor of succinate dehydrogenase (SDH), significantly attenuated succinate accumulation, reduced the oxidative stress and iron levels, and mitigated the severity of the seizures and neuronal injury. Our results thus indicate that the accumulation of succinate due to the reverse catalysis of SDH may exacerbate oxidative stress and thus induce iron accumulation and neuronal injury in both models. Targeting succinate accumulation may achieve neuroprotective and anti-seizure effects. Highlights: KA- and PTZ-induced seizures were accompanied by succinate accumulation. Succinate accumulation contributes to the elevated ROS and iron levels. Succinate accumulation may be due to inverse catalysis of SDH from fumarate. Inhibiting succinate accumulation relieved ROS and iron levels. Inhibiting succinate accumulation attenuated neuronal injury and seizure.